2022
DOI: 10.1515/res-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Preservation Practices for Information Resources in Public University Libraries in Tanzania

Abstract: The present study examined the preservation practices for information resources in seven public university libraries in Tanzania. Convenient and purposive sampling techniques were used to recruit library staff and library directors respectively to participate in the study. Data were collected through questionnaires and semi-structured interviews. The quantitative data obtained from the questionnaires were analysed using the Statistical Product and Service Solution (version 20) software while the qualitative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Similarly, another survey amongst 113 librarians from 10 universities in Nigeria also reported a higher prevalence of the practices like using stable media and replication (91%), checking data for errors (84%), retaining the necessary hardware/software (86%), implementing antivirus software (98%) and media refreshing (69%) (Nworie, 2019). In a recent study, Mubofu et al (2022) revealed that Tanzania's public university libraries apply a variety of strategies for preserving information resources, whereas binding, digitization, migration and emergency preparedness plans were practiced at large. The study recommended to train librarians in digital preservation strategies to improve the situation.…”
Section: Technical Practicesmentioning
confidence: 99%
“…Similarly, another survey amongst 113 librarians from 10 universities in Nigeria also reported a higher prevalence of the practices like using stable media and replication (91%), checking data for errors (84%), retaining the necessary hardware/software (86%), implementing antivirus software (98%) and media refreshing (69%) (Nworie, 2019). In a recent study, Mubofu et al (2022) revealed that Tanzania's public university libraries apply a variety of strategies for preserving information resources, whereas binding, digitization, migration and emergency preparedness plans were practiced at large. The study recommended to train librarians in digital preservation strategies to improve the situation.…”
Section: Technical Practicesmentioning
confidence: 99%
“…Although the security of library material is essential to its effective exploitation or use due to knowledge expansion, compound factors disturb the protection of library resources. Previous studies have reported that application of ESSs emanate from human factors, organizational factors and technological factors (Masenya and Chisita, 2022;Mubofu et al, 2022;Ngamba and Casmir, 2021;Chisenga, 2016& Maidabino, 2010. This paper reviewed various types of literature relating to the application of ESSs in academic libraries and the challenges they are bumped into and eventually propose various methods that academic libraries can deploy to address the challenges.…”
Section: Challenges Hindering the Application Of Electronic Security ...mentioning
confidence: 99%
“…Another previous study by Mubofu, Mambo, and Samzugi (2022) stated that the preservation techniques carried out in state university libraries in Tanzania were binding, digitization, migration, and emergency preparedness planning. This study also found that migration, technological preservation, binding, proper shelving, and cleanliness of storage areas were preservation strategies recommended by respondents in public university libraries.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, it can be concluded that state university libraries have various approaches to preserving print and digital information sources. The difference between the study conducted by Mubofu, Mambo, and Samzugi (2022) and the researchers lies in the research method used, namely mixed methods, while the researchers used descriptive qualitative. Apart from that, the selection of research samples used was also different, this previous study used convenience sampling while the researchers used purposive sampling.…”
Section: Introductionmentioning
confidence: 99%